THE FORMALIZATION PROCESS OF CARGO TERMINAL OPERATION - N. Yu. Shramenko (Nauka ta progres transportu, 2011)
The mathematical formalization of operation process for a terminal complex is proposed and a model taking into account characteristics of a freight terminal and all the possible states of a system is developed.